2008
DOI: 10.1007/s00330-008-0982-1
|View full text |Cite
|
Sign up to set email alerts
|

Global left-ventricular function assessment using dual-source multidetector CT: effect of improved temporal resolution on ventricular volume measurement

Abstract: The purpose was to compare global left-ventricular (LV) function parameters measured with cine MRI with results from multiphase dual-source CT (DSCT) using 10 and 20 reconstruction phases. Twenty-eight patients with suspected or known CAD underwent DSCT coronary angiography. LV end-diastolic (EDV), end-systolic (ESV) and stroke volumes (SV), and ejection fraction (EF) were determined using LV segmentation and selection of specific phases from DSCT image sets reconstructed either at 5% or 10% steps through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…In the recent past, 64-row CT has greatly advanced as a noninvasive method for coronary angiography and also has been found to allow accurate assessment of LV function (13)(14)(15)34). For EF, the limits of agreement obtained with 64-row CT (Ϯ14.2%) in comparison with MRI were similar to those reported in previous studies using 64-row CT by Guo Comparative Per-Patient Diagnostic Performance for Regional Function Table 2.…”
Section: Discussionsupporting
confidence: 83%
“…In the recent past, 64-row CT has greatly advanced as a noninvasive method for coronary angiography and also has been found to allow accurate assessment of LV function (13)(14)(15)34). For EF, the limits of agreement obtained with 64-row CT (Ϯ14.2%) in comparison with MRI were similar to those reported in previous studies using 64-row CT by Guo Comparative Per-Patient Diagnostic Performance for Regional Function Table 2.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have analyzed test performance of this segmentation algorithm for the assessment of cardiac function by comparing it with manual contour tracing, 15,19,20 echocardiography, or MRI, 20,21 but there is a lack of evidence for test performance for mass estimates, and, to the best of our knowledge, none of the existing studies addresses reproducibility between independent scans in the same group of patients.…”
Section: Discussionmentioning
confidence: 98%
“…However, reconstructions at intervals of 10% are thought to be adequate for clinical use according to Suzuki et al [27]. In addition, it was reported that DSCT and MRI show similar differences in functional parameters when 10 or 20 phases are used for reconstruction of the DSCT data [28]. …”
Section: Discussionmentioning
confidence: 99%